2022
DOI: 10.3389/fphar.2022.1018473
|View full text |Cite
|
Sign up to set email alerts
|

Molecular docking and biochemical validation of (-)-syringaresinol-4-O-β-D-apiofuranosyl-(1→2)-β-D-glucopyranoside binding to an allosteric site in monoamine transporters

Abstract: Albizia julibrissin Durazz is one of the most common herbs used for depression and anxiety treatment, but its mechanism of action as an antidepressant or anxiolytic drug have not been fully understood. We previously isolated and identified one lignan glycoside compound from Albizia Julibrissin Durazz, (-)-syringaresinol-4-O-β-D-apiofuranosyl-(1→2)-β-D-glucopyranoside (SAG), that inhibited all three monoamine transporters with a mechanism of action different from that of the conventional antidepressants. In thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 67 publications
0
9
0
Order By: Relevance
“…Many experimental and computational studies have suggested that allosteric sites exist in MATs. ,, In 2016, Coleman et al successfully resolved the crystal structures of SERT bound with escitalopram in its allosteric site (S2 site), providing strong evidence for the allosteric mechanism . The allosteric sites of MATs are usually aromatic and hydrophobic pocket positioned in the extracellular vestibule. , Occupation of S2 site by allosteric modulators has the potential to be a fast-acting and safe new strategy for the treatment of physiological disorders by affecting the binding and dissociation of substrates and the conformational change of protein. , To date, many allosteric modulators of MATs have been designed as potential therapeutic agents. ,,,, …”
Section: Structure and Function Of Slcsmentioning
confidence: 99%
See 4 more Smart Citations
“…Many experimental and computational studies have suggested that allosteric sites exist in MATs. ,, In 2016, Coleman et al successfully resolved the crystal structures of SERT bound with escitalopram in its allosteric site (S2 site), providing strong evidence for the allosteric mechanism . The allosteric sites of MATs are usually aromatic and hydrophobic pocket positioned in the extracellular vestibule. , Occupation of S2 site by allosteric modulators has the potential to be a fast-acting and safe new strategy for the treatment of physiological disorders by affecting the binding and dissociation of substrates and the conformational change of protein. , To date, many allosteric modulators of MATs have been designed as potential therapeutic agents. ,,,, …”
Section: Structure and Function Of Slcsmentioning
confidence: 99%
“…Since 2005, the first X-ray crystal structure (PDB ID: 2A65) of the bacterial leucine transporter (LeuT) was reported, and the structures of the LeuT, drosophila dopamine transporter (dDAT), and SERT have been used as templates for the construction of structural models of MATs. ,, Fu et al also modeled a large number of structural variabilities of SCLs by homology modeling and added them to the VARIDT database () . Recently, the popular AI protein structure prediction method AlphaFold2 can also be used to accurately predict transporter structures. , These structural models obtained by computational techniques greatly enrich the structural information on SLCs and are widely used in drug design and transport mechanism studies. , Nevertheless, the application of computational structures in drug design still faces several challenges; the accuracy of models and diversity of conformations need to be carefully considered . Considering that conformational changes of proteins are closely related to their function, studying the multiple conformations of SLCs is helpful to understand their transport mechanism.…”
Section: Structure and Function Of Slcsmentioning
confidence: 99%
See 3 more Smart Citations